Toxic chemicals used in wars - Abd Razak, Dzulkifli (1995)
WAR SEEMS TO BE PART AND PARCEL of the modern contemporary life. Despite the sufferings that it caused, man is still are very much preoccupied with it. Warriors' Day is one occassion that serves to remind us how dreaded war is, and Malaysia has had its fair share of the effects of war. Yesterday, Malaysia paid tribute to her heroes and their families who have sacrificed their lives in defending the honour of the country. As we recall those sad moments of war, perhaps it is time for us to reflect at the kind of dangers that our soldiers can be exposed to especially in these days where deadly gases, bombs and microorganisms become part and parcel of war.